Age-related Differences in Immune Reactions to SARS-CoV-2 Spike and Nucleocapsid Antigens - Morhart, Patrick; Kehl, Sven; Schuh, Wolfgang; Hermes, Katharina; Meltendorf, Stefan; Neubert, Antje; Schneider, Michael; Brunner-Weinzierl, Monika; Schneider, Holm; Lingel, Holger (In Vivo, 2023)
Background/Aim: The manifestation and severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections show a clear correlation to the age of a patient. The younger a person, the less likely the infection results in significant illness. To explore the immunological characteristics behind this phenomenon, we studied the course of SARS-CoV-2 infections in 11 households, including 8 children and 6 infants/neonates of women who got infected with SARS-CoV-2 during pregnancy. Materials and Methods: We investigated the immune responses of peripheral blood mononuclear cells (PBMCs), umbilical cord blood mononuclear cells (UCBCs), and T cells against spike and nucleocapsid antigens of SARS-COV-2 by flow cytometry and cytokine secretion assays. Results: Upon peptide stimulation, UCBC from neonates showed a strongly reduced IFN-γ production, as well as lower levels of IL-5, IL-13, and TNF-α alongside with decreased frequencies of surface CD137/PD-1 co-expressing CD4+ and CD+8 T cells compared with adult PBMCs. The PBMC response of older children instead was characterized by elevated frequencies of IFN-γ+ CD4+ T cells, but significantly lower levels of multiple cytokines (IL-5, IL-6, IL-9, IL-10, IL-17A, and TNF-α) and a marked shift of the CD4+/CD8+ T-cell ratio towards CD8+ T cells in comparison to adults. Conclusion: The increased severity of SARS-CoV-2 infections in adults could result from the strong cytokine production and lower potential to immunomodulate the excessive inflammation, while the limited IFN-γ production of responding T cells in infants/neonates and the additional higher frequencies of CD8+ T cells in older children may provide advantages during the course of a SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2023-01-13
Keywords: children; COVID-19; immune response; inflammation; neonates; pediatric immunology; SARS-CoV-2; spike protein

Aggregation tests identify new gene associations with breast cancer in populations with diverse ancestry - Mueller, Stefanie H.; Lai, Alvina G.; Valkovskaya, Maria; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Lush, Michael; Abu-Ful, Zomoruda; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; et al. (Genome Medicine, 2023)
Background: Low-frequency variants play an important role in breast cancer (BC) susceptibility. Gene-based methods can increase power by combining multiple variants in the same gene and help identify target genes. Methods: We evaluated the potential of gene-based aggregation in the Breast Cancer Association Consortium cohorts including 83,471 cases and 59,199 controls. Low-frequency variants were aggregated for individual genes’ coding and regulatory regions. Association results in European ancestry samples were compared to single-marker association results in the same cohort. Gene-based associations were also combined in meta-analysis across individuals with European, Asian, African, and Latin American and Hispanic ancestry. Results: In European ancestry samples, 14 genes were significantly associated (q < 0.05) with BC. Of those, two genes, FMNL3 (P = 6.11 × 10−6) and AC058822.1 (P = 1.47 × 10−4), represent new associations. High FMNL3 expression has previously been linked to poor prognosis in several other cancers. Meta-analysis of samples with diverse ancestry discovered further associations including established candidate genes ESR1 and CBLB. Furthermore, literature review and database query found further support for a biologically plausible link with cancer for genes CBLB, FMNL3, FGFR2, LSP1, MAP3K1, and SRGAP2C. Conclusions: Using extended gene-based aggregation tests including coding and regulatory variation, we report identification of plausible target genes for previously identified single-marker associations with BC as well as the discovery of novel genes implicated in BC development. Including multi ancestral cohorts in this study enabled the identification of otherwise missed disease associations as ESR1 (P = 1.31 × 10−5), demonstrating the importance of diversifying study cohorts.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Breast cancer susceptibility; Diverse ancestry; Gene regulation; Genome-wide association study; Rare variants

Ambulante Geburtseinleitung: Wann und wie? - Kehl, Sven; Bader, Simon; Anetsberger, Daniel; Schneider, Michael (Die Gynäkologie, 2024)
The induction of labor has evolved over the past few decades. This article explores the medical foundations, current indications and advances, particularly in the realm of outpatient induction of labor. Individual risk-benefit analyses are crucial and guidelines (Association of the Scientific Medical Societies in Germany, AWMF register nr. 015/088) provide recommendations. Outpatient induction of labor offers advantages, such as resource utilization and patient satisfaction. Mechanical methods (balloon catheters, hygroscopic dilators) and pharmacological approaches (dinoprostone, misoprostol) are discussed. Balloon catheters are considered safe and effective and suitable for outpatient induction of labor. Prostaglandins and castor oil are not recommended in the outpatient setting due to the associated risks. In summary, outpatient induction of labor is feasible in selected cases but requires meticulous planning and individual consideration of various aspects.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Cesarean section; Dinoprostone; Misoprostol; Patient satisfaction; Prostaglandin

Analysis of GDF15 and IGFBP7 in Hyperemesis Gravidarum Support Causality - Fejzo, Marlena S.; Fasching, Peter; Schneider, Michael; Schwitulla, Judith; Beckmann, Matthias; Schwenke, Eva; Macgibbon, Kimber W.; Mullin, Patrick M. (Geburtshilfe und Frauenheilkunde, 2019)
Objective Hyperemesis gravidarum, severe nausea and vomiting in pregnancy, occurs in up to 2% of pregnancies and leads to significant weight loss, dehydration, electrolyte imbalance, and ketonuria. It is associated with both maternal and fetal morbidity. Familial aggregation studies and twin studies suggest a genetic component. In a recent GWAS, we showed that placentation, appetite, and cachexia genes GDF15 and IGFBP7 are linked to hyperemesis gravidarum (HG). The purpose of this study is to determine whether GDF15 and IGFBP7 are upregulated in HG patients. Methods We compared serum levels of GDF15 and IGFBP7 at 12 and 24 weeks' gestation in women hospitalized for HG, and two control groups, women with nausea and vomiting of pregnancy (NVP), and women with no NVP. Results We show GDF15 and IGFBP7 serum levels are significantly increased in women with HG at 12 weeks' gestation. Serum levels of hCG are not significantly different between cases and controls. At 24 weeks gestation, when symptoms have largely resolved, there is no difference in GDF15 and IGFBP7 serum levels between cases and controls. Conclusion This study supports GDF15 and IGFBP7 in the pathogenesis of HG and may be useful for prediction and diagnosis. The GDF15-GFRAL brainstem-activated pathway was recently identified and therapies to treat conditions of abnormal appetite are under intense investigation. Based on our findings, HG should be included.
CRIS-Team Scopus Importer:2019-05-02
Keywords: GDF15; GFRAL; hyperemesis gravidarum; IGFBP7; nausea and vomiting of pregnancy

Automatic Disentanglement of Motion in Fetal Low Field MRI Scans - Kitzberger, Michael; Silva, Sara Neves; Verdera, Jordina Aviles; Rojas, Diego Fajardo; Uus, Alena; Schulz-Heise, Susanne; Schmidt, Sandy; Schneider, Michael; Story, Lisa; Uder, Michael; Rutherford, Mary; Hutter, Jana (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2025)
Fetal dynamic MRI acquisitions allow insights into fetal motor behaviour, serving as a surrogate for fetal cognitive development. Systematic assessment of these highly temporally resolved 2D images might hence allow novel insights into both normal development and contain crucial information in pathology. Here, we present an automatic deep learning-based assessment for masking of the uterine and fetal structures and fetal and maternal motion quantification tool, applied to 61 low field 0.55T fetal cine MRI datasets acquired between 24 and 40 weeks gestational age at two sites using two different MR contrasts. The lack of cine labels was overcome by imitating cine acquisitions from high-resolution labelled static 3D anatomical balanced steady-state free precession datasets. Results illustrate high segmentation accuracy for the larger uterine structures (mean dice coefficient of 0.86 for the fetal body, 0.88 for the fetal head, 0.61 for the placenta) as well as the ability to detect fetal motion.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Cine; Fetal MRI; Motion assessment

Boosting distributional copula regression - Hans, Nicolai; Klein, Nadja; Faschingbauer, Florian; Schneider, Michael; Mayr, Andreas (Biometrics, 2022)
Capturing complex dependence structures between outcome variables (e.g., study endpoints) is of high relevance in contemporary biomedical data problems and medical research. Distributional copula regression provides a flexible tool to model the joint distribution of multiple outcome variables by disentangling the marginal response distributions and their dependence structure. In a regression setup, each parameter of the copula model, that is, the marginal distribution parameters and the copula dependence parameters, can be related to covariates via structured additive predictors. We propose a framework to fit distributional copula regression via model-based boosting, which is a modern estimation technique that incorporates useful features like an intrinsic variable selection mechanism, parameter shrinkage and the capability to fit regression models in high-dimensional data setting, that is, situations with more covariates than observations. Thus, model-based boosting does not only complement existing Bayesian and maximum-likelihood based estimation frameworks for this model class but rather enables unique intrinsic mechanisms that can be helpful in many applied problems. The performance of our boosting algorithm for copula regression models with continuous margins is evaluated in simulation studies that cover low- and high-dimensional data settings and situations with and without dependence between the responses. Moreover, distributional copula boosting is used to jointly analyze and predict the length and the weight of newborns conditional on sonographic measurements of the fetus before delivery together with other clinical variables.
CRIS-Team WoS Importer:2022-10-21

Breast cancer risk - From genetics to molecular understanding of pathogenesis - Fasching, Peter; Ekici, Arif Bülent; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Schneider, Michael; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Several advancements over the last decade have triggered the developments in the field of breast cancer risk research. One of them is the availability of the human genome sequence along with cheap genotyping possibilities. Another is the globalization of research, which has led to the growth of research collaboration into large international consortia that facilitate the pooling of clinical and genotype data of hundreds of thousands of patients and healthy control individuals. This review concerns with the recent developments in breast cancer risk research and focuses on the discovery of new genetic breast cancer risk factors and their meaning in the context of established non-genetic risk factors. Finally the clinical application is highly dependent on the accuracy of breast cancer risk prediction models, not only for all breast cancer patients, but also for molecular subtypes, preferably for those which are associated with an unfavorable prognosis. Recently risk prediction incorporates all possible risk factors, which include epidemiological risk factors, mammographic density and genetic risk factors. © Georg Thieme Verlag KG Stuttgart• New York•.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA; breast cancer risk; gene-environment interaction; genetic risk factors; prediction models

Can Sonographic Fetal Biometry Predict Adverse Perinatal Outcome? - Pretscher, Jutta; Schwenke, Eva; Baier, Friederike; Kehl, Sven; Schneider, Michael; Stumpfe, Florian Matthias; Schmid, Matthias; Beckmann, Matthias; Mayr, Andreas; Schild, Ralf; Faschingbauer, Florian (Ultraschall in der Medizin, 2019)
Objective To evaluate the association of sonographic fetal biometry (sonographic head circumference (soHC), sonographic abdominal circumference (soAC), estimated fetal weight (EFW)) with mode of delivery and adverse perinatal outcome. Methods Singleton pregnancies with a gestational age ≥ 37 weeks and an ultrasound examination with complete biometric parameters within 7 days before delivery were retrospectively included. The association between soHC, soAC, EFW and fetal (5-min Apgar < 7, pH < 7.1, neonatal intensive care unit (NICU) admission, shoulder dystocia (ShD)) and maternal (obstetric intervention (OI): caesarean or vaginal operative delivery, obstetric anal sphincter injury syndrome (OASIS), postpartum hemorrhage (pph)) adverse outcomes were analyzed using univariate and multivariate logistic regression analyses. Results 12 396 women were included and 3479 (28.07 %) needed an OI. Multivariate analyses demonstrated significant contributions for the prediction of OI by soHC and soAC, whereas EFW did not reach significance. The highest OR was shown for soHC (1087, p < 0.001). ShD occurred in 73 (0.59 %) of the deliveries. Multivariate analyses showed that significant contributions for the prediction of ShD were provided only by soAC (OR 1460, p = 0.007). For the other maternal and neonatal adverse outcome parameters, no significant association with the biometric measurements could be demonstrated in the multivariate analyses. The overall detection rates for the prediction of adverse perinatal outcome by the different biometric parameters and EFW were poor. Conclusion Obstetric management decisions should not be based solely on measurements of biometric parameters or EFW.
CRIS-Team Scopus Importer:2019-05-02
Keywords: adverse perinatal outcome; biometric parameters; fetal weight estimation; mode of delivery; ultrasound

Cerebroplacental versus Umbilicocerebral Ratio—Analyzing the Predictive Value Regarding Adverse Perinatal Outcomes in Low- and High-Risk Fetuses at Term - Stumpfe, Florian; Mayr, Andreas; Schneider, Michael; Kehl, Sven; Stübs, Frederik; Antoniadis, Sophia; Titzmann, Adriana; Pontones, Constanza; Bayer, Christian M.; Beckmann, Matthias; Faschingbauer, Florian (Medicina, 2023)
Background and Objectives: The aim of this study was to investigate the prediction of adverse perinatal outcomes using the cerebroplacental (CPR) and umbilicocerebral (UCR) ratios in different cohorts of singleton pregnancies. Materials and Methods: In this retrospective cohort study, we established our own Multiple of Median (MoM) for CPR and UCR. The predictive value for both ratios was studied in the following outcome parameters: emergency cesarean delivery, operative intervention (OI), OI due to fetal distress, 5-min Apgar < 7, admission to neonatal intensive care unit, and composite adverse perinatal outcome. The performance of the ratios was assessed in the following cohorts: total cohort (delivery ≥ 37 + 0 weeks gestation, all birth weight centiles), low-risk cohort (delivery ≥ 37 + 0 weeks gestation, birth weight ≥ 10. centile), prolonged pregnancy cohort (delivery ≥ 41 + 0 weeks gestation, birth weight ≥ 10. centile) and small-for-gestational-age fetuses (delivery ≥ 37 + 0 weeks gestation, birth weight < 10. centile). The underlying reference values for MoM were estimated using quantile regression depending on gestational age. Prediction performance was evaluated using logistic regression models assessing the corresponding Brier score, combining discriminatory power and calibration. Results: Overall, 3326 cases were included. Across all cohorts, in the case of a significant association between a studied outcome parameter and CPR, there was an association with UCR, respectively. The Brier score showed only minimal differences for both ratios. Conclusions: Our study provides further evidence regarding predictive values of CPR and UCR. The results of our study suggest that reversal of CPR to UCR does not improve the prediction of adverse perinatal outcomes.
CRIS-Team Scopus Importer:2023-09-08
Keywords: cerebroplacental ratio; CPR; UCR; umbilicocerebral ratio

Clinical and pathological associations of PTEN expression in ovarian cancer: a multicentre study from the Ovarian Tumour Tissue Analysis Consortium - Martins, Filipe Correia; Couturier, Dominique Laurent; Paterson, Anna; Karnezis, Anthony N.; Chow, Christine; Nazeran, Tayyebeh M.; Odunsi, Adekunle; Gentry-Maharaj, Aleksandra; Vrvilo, Aleksandra; Hein, Alexander; Talhouk, Aline; Osorio, Ana; et al. (British Journal of Cancer, 2020)
Background: PTEN loss is a putative driver in histotypes of ovarian cancer (high-grade serous (HGSOC), endometrioid (ENOC), clear cell (CCOC), mucinous (MOC), low-grade serous (LGSOC)). We aimed to characterise PTEN expression as a biomarker in epithelial ovarian cancer in a large population-based study. Methods: Tumours from 5400 patients from a multicentre observational, prospective cohort study of the Ovarian Tumour Tissue Analysis Consortium were used to evaluate associations between immunohistochemical PTEN patterns and overall survival time, age, stage, grade, residual tumour, CD8+ tumour-infiltrating lymphocytes (TIL) counts, expression of oestrogen receptor (ER), progesterone receptor (PR) and androgen receptor (AR) by means of Cox proportional hazard models and generalised Cochran–Mantel–Haenszel tests. Results: Downregulation of cytoplasmic PTEN expression was most frequent in ENOC (most frequently in younger patients; p value = 0.0001) and CCOC and was associated with longer overall survival in HGSOC (hazard ratio: 0.78, 95% CI: 0.65–0.94, p value = 0.022). PTEN expression was associated with ER, PR and AR expression (p values: 0.0008, 0.062 and 0.0002, respectively) in HGSOC and with lower CD8 counts in CCOC (p value < 0.0001). Heterogeneous expression of PTEN was more prevalent in advanced HGSOC (p value = 0.019) and associated with higher CD8 counts (p value = 0.0016). Conclusions: PTEN loss is a frequent driver in ovarian carcinoma associating distinctly with expression of hormonal receptors and CD8+ TIL counts in HGSOC and CCOC histotypes.
CRIS-Team Scopus Importer:2020-06-26

Correlation of short-term variation and Doppler parameters with adverse perinatal outcome in low-risk fetuses at term - Stumpfe, Florian M.; Kehl, Sven; Pretscher, Jutta; Baier, Friederike; Bayer, Christian M.; Schwenke, Eva; Schneider, Michael; Mayr, Andreas; Schild, Ralf L.; Schmid, Matthias; Beckmann, Matthias; Faschingbauer, Florian (Archives of Gynecology and Obstetrics, 2019)
ObjectiveTo evaluate the association of short-term variation (STV) and Doppler parameters with adverse perinatal outcome in low-risk fetuses at term.MethodsThis was a retrospective study of 1008 appropriate-for-gestational age (AGA) term fetuses. Doppler measurements [umbilical artery (UA), middle cerebral artery (MCA), and cerebroplacental ratio (CPR)] and computerized CTG (cCTG) with STV analysis were performed prior to active labor (4cm cervical dilatation) within 72h of delivery. The association between Doppler indices and STV values with adverse perinatal outcome was analyzed using univariate regression analysis.ResultsNo significant association between Doppler parameters and the need for secondary cesarean delivery (CD) or operative vaginal delivery (OVD) was shown. Regarding fetuses delivered by CD due to fetal distress, regression analyzes revealed significantly higher UA PI MoM. However, the differences in MCA PI MoM and CPR MoM were not statistically significant. Fetuses with the need for emergency CD showed significantly higher UA PI MoM, lower MCA PI MoM and lower CPR MoM. Neonates with a 5-min Apgar score <7 had significantly lower MCA PI MoM and neonatal acidosis (UA pH 7.10) showed a significant association with UA PI MoM. None of the assessed outcome parameters were significantly associated to STV.ConclusionDoppler indices assessed close to delivery in low-risk fetuses at term show a moderate association with adverse outcome parameters,whereas STV does not appear to predict poor perinatal outcome in this group of fetuses.
CRIS-Team WoS Importer:2019-03-08

Correlation of short-term variation and Doppler parameters with adverse perinatal outcome in small-for-gestational age fetuses at term - Stumpfe, Florian M.; Faschingbauer, Florian; Kehl, Sven; Pretscher, Jutta; Stelzl, Patrick; Mayr, Andreas; Schild, Ralf L.; Schmid, Matthias; Beckmann, Matthias; Schneider, Michael (Archives of Gynecology and Obstetrics, 2019)
Objective: To evaluate the association of short-term variation (STV) and Doppler parameters with adverse perinatal outcome in small-for-gestational-age (SGA) fetuses at term. Methods: In this retrospective single-center study 97 patients with singleton SGA fetuses at term (≥ 37 + 0 weeks’ gestation) were examined. Inclusion criteria were a birth weight < 10th centile, cephalic presentation and planned vaginal birth. Only cases with available Doppler measurements of umbilical artery (UA) and middle cerebral artery (MCA) with calculated cerebroplacental ratio (CPR) in combination with a computerized CTG (cCTG) and STV 72 h prior to delivery were eligible for analysis. Pulsatility indices (PI) were converted into multiples of median (MoM), adjusted for gestational age. The association between Doppler indices and STV values with mode of delivery [secondary cesarean delivery (CD), operative vaginal delivery (OVD), as well as secondary CD and OVD due to fetal distress] and neonatal outcome [UA blood pH ≤ 7.15 and the need of admission to the neonatal intensive care unit (NICU)] was analyzed using logistic regression analysis. Results: There was a significant association between UA PI MoM and the rate of CD. CD due to fetal distress, OVD and OVD due to fetal distress did not show a correlation with the evaluated Doppler parameters. Furthermore, we did not find an association between low UA birth pH and Doppler parameters while neonates with the need of admission to NICU had significant higher UA PI MoM and significant lower MCA PI MoM and CPR MoM. Regarding STV, a significant effect of low STV on NICU admission was found while none of the other assessed outcome parameters were significantly associated with STV. Conclusion: STV and Doppler parameters in SGA fetuses at term are significantly associated to the rate of NICU admission.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Cardiotocography; Cerebroplacental ratio; Computerized CTG; Doppler; Fetal distress; SGA; Short-term variation; small-for-gestational age

Feasibility and Acceptance of Self-Guided Mobile Ultrasound among Pregnant Women in Routine Prenatal Care - Pontones, Constanza; Titzmann, Adriana; Hübner, Hanna; Danzberger, Nina; Rübner, Matthias; Häberle, Lothar; Eskofier, Björn; Nissen, Michael; Kehl, Sven; Faschingbauer, Florian; Beckmann, Matthias; Fasching, Peter; et al. (Journal of Clinical Medicine, 2023)
Background and objectives: Mobile and remote ultrasound devices are becoming increasingly available. The benefits and possible risks of self-guided ultrasound examinations conducted by pregnant women at home have not yet been well explored. This study investigated aspects of feasibility and acceptance, as well as the success rates of such examinations. Methods: In this prospective, single-center, interventional study, forty-six women with singleton pregnancies between 17 + 0 and 29 + 6 weeks of gestation were included in two cohorts, using two different mobile ultrasound systems. The participants examined the fetal heartbeat, fetal profile and amniotic fluid. Aspects of feasibility and acceptance were evaluated using a questionnaire. Success rates in relation to image and video quality were evaluated by healthcare professionals. Results: Two thirds of the women were able to imagine performing the self-guided examination at home, but 87.0% would prefer live support by a professional. Concerns about their own safety and that of the child were expressed by 23.9% of the women. Success rates for locating the target structure were 52.2% for videos of the fetal heartbeat, 52.2% for videos of the amniotic fluid in all four quadrants and 17.9% for videos of the fetal profile. Conclusion: These results show wide acceptance of self-examination using mobile systems for fetal ultrasonography during pregnancy. Image quality was adequate for assessing the amniotic fluid and fetal heartbeat in most participants. Further studies are needed to determine whether ultrasound self-examinations can be implemented in prenatal care and how this would affect the fetomaternal outcome.
CRIS-Team Scopus Importer:2023-07-28
Keywords: acceptance; feasibility; mobile ultrasound; pregnancy; prenatal care; self-guided ultrasound

Genetic variants in the genes of the sex steroid hormone metabolism and depressive symptoms during and after pregnancy - Schneider, Michael; Pretscher, Jutta; Goecke, Tamme; Häberle, Lothar; Engel, Anne; Kornhuber, Johannes; Eichler, Anna; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aim of this study was to conduct an association analysis of depressive symptoms and polymorphisms in the ESR1, PGR, CYP19A1, and COMT genes in pregnant and postpartum women. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for assessment of maternal and fetal health. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of pregnancy, visit 2 was shortly after birth, and visit 3 was 6–8 months after birth. Germline DNA and depression measurements from 361 pregnant women were available for analysis. Six single nucleotide polymorphisms (SNPs) in the above-mentioned genes were genotyped. After reconstruction of haplotypes for PGR (rs1042838 and rs10895068) and CYP19A1 (rs10046 and rs4646), a multifactorial linear mixed model was applied to the data to describe the association between haplotypes and depression values. The single SNPs for ESR1 (rs488133) and COMT (rs4680) were analyzed separately using linear mixed models analogously. Results: The mean antepartum EPDS measurement was 5.1, the mean postpartal measurement after 48–72 h was 3.5, and the mean value 6–8 months postpartum was 4.2. The SNPs in PGR were reconstructed into three haplotypes. The most common haplotype was GG, with 63.43% of patients carrying two copies and 33.52% carrying one copy. For haplotype GA, the group of carriers of two copies (0.28%) was combined with the carriers of one copy (9.70%). Haplotype reconstruction using CYP19A1 SNPs resulted in three haplotypes. The most common haplotype was TC, with 25.48% of patients carrying two copies and 51.52% one copy. None of the haplotype blocks and neither of the two single SNPs showed any significant associations with EPDS values. Conclusions: The candidate haplotypes analyzed in PGR and CYP19A1 and single SNPs in ESR1 and COMT did not show any association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
CRIS-Team Scopus Importer:2022-06-17
Keywords: COMT; CYP19A1; Depression; EPDS; ESR1; PGR; Single nucleotide polymorphisms

Genetic variants in the glucocorticoid pathway genes and birth weight - Schneider, Michael; Hübner, Theresa; Pretscher, Jutta; Goecke, Tamme W.; Schwitulla, Judith; Häberle, Lothar; Kornhuber, Johannes; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: The aim of this study was to examine associations between single nucleotide polymorphisms (SNPs) that tag genetic variation in the glucocorticoid pathways (particularly in maternal genes FKBP5, NR3C1, and CRHR1) and birth weight. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health. Germline DNA was collected from 375 pregnant women. Nine SNPs in the above-mentioned genes were genotyped. After reconstruction of haplotypes for each gene, a linear regression model was applied to the data to describe the association between haplotypes and birth weight. Results: Female sex in the newborn (compared to male) was associated with lower birth weight, whereas a later week of gestation, higher body mass index pre-pregnancy, and higher parity were associated with higher birth weight. No association with birthweight was shown for the haplotypes of the selected SNPs. Conclusions: In this cohort of healthy unselected pregnant women, the analyzed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show any association with birth weight. This might be in line with several other studies that have found no influence of fetal polymorphisms in the glucocorticoid receptor gene or triggers of the maternal HPA axis such as stress and psychosocial problems on birth weight. However, the small sample size in this study and the lack of consideration of individual risk factors and levels of stress in this cohort needs to be taken into account when interpreting the results.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Birth weight; CRHR1; FKBP5; NR3C1; Single nucleotide polymorphisms

Genetic variations in estrogen and progesterone pathway genes in preeclampsia patients and controls in Bavaria - Pretscher, Jutta; Rübner, Matthias; Ekici, Arif Bülent; Rödl, Melanie; Hübner, Hanna; Schwitulla, Judith; Titzmann, Adriana; Hartwig, Charlotte; Beckmann, Matthias; Fasching, Peter; Schneider, Michael; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: Hypertensive pregnancy disorders and preeclampsia are major causes of maternal and fetal morbidity and mortality worldwide. Many different organs are involved in the diseases’ clinical phenotype. The underlying mechanism is still unknown, with a possible genetic component. This case–control study investigated effects on the risk of preeclampsia of genetic variations (single nucleotide polymorphisms, SNPs) in the estrogen and progesterone pathway genes. Methods: The study included 167 patients with preeclampsia and 115 healthy controls from the “Franconian Maternal Health Evaluation Studies” (FRAMES). All patients completed an epidemiological questionnaire, data from which were correlated with prospective data on pregnancy and labor. DNA was isolated from blood samples and genotyping was done by PCR. Variants in the aromatase gene CYP19A1 (rs10046, rs4646), progesterone receptor gene (rs1042838, rs10895068), and estrogen receptor-α gene (rs488133) were examined, and the genotype distribution in the two groups was analyzed statistically. Results: A significant difference in the distribution frequency of genotypes between preeclampsia patients and controls was identified in one of the five SNPs. For rs10895068 in the progesterone receptor gene, genotype G/A was significantly more frequent among cases than controls (P = 0.023). No significant differences between the two cohorts were found in the other SNPs. Conclusions: This study showed a significant association between only one SNP in the progesterone receptor and preeclampsia. Other studies have also noted genetic aspects of preeclampsia. The underlying mechanism and causal relationship are not yet known, and further research is needed to explain the extent of genetic variations and the causal relationship in preeclampsia.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Genetic marker; Preeclampsia; Pregnancy; Single nucleotide polymorphism (SNP)

Induction of Labour In Growth Restricted and Small for Gestational Age Fetuses - A Historical Cohort Study - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Berlit, Sebastian; Grosse-Steffen, Thomas; Faschingbauer, Florian; Suetterlin, Marc; Beckmann, Matthias; Schneider, Michael (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Purpose Induction of labour for small-for-gestational-age (SGA) foetus or intrauterine growth restriction (IUGR) is common, but data are limited. The aim of this trial was therefore to compare labour induction for SGA/IUGR with cases with normal fetal growth beyond the 10th percentile.
CRIS-Team WoS Importer:2019-03-15

Induction of Labour in Growth Restricted and Small for Gestational Age Foetuses - A Historical Cohort Study. - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Berlit, Sebastian; Grosse-Steffen, Thomas; Faschingbauer, Florian; Suetterlin, Marc; Beckmann, Matthias; Schneider, Michael (Geburtshilfe und Frauenheilkunde, 2019)
Purpose Induction of labour for small-for-gestational-age (SGA) foetus or intrauterine growth restriction (IUGR) is common, but data are limited. The aim of this study was therefore to compare labour induction for SGA/IUGR with cases of normal foetal growth above the 10th percentile. Material and Methods This historical multicentre cohort study included singleton pregnancies at term. Labour induction for SGA/IUGR (IUGR group) was compared with cases of foetal growth above the 10th percentile (control group). Primary outcome measure was caesarean section rate. Results The caesarean section rate was not different between the 2 groups (27.0 vs. 26.2%, p = 0.9154). In the IUGR group, abnormal CTG was more common (30.8 vs. 21.9%, p = 0.0214), and foetal blood analysis was done more often (2.5 vs. 0.5%, p = 0.0261). There were more postpartum transfers to the NICU in the IUGR group (40.0 vs. 12.8%, p < 0.0001), too. Conclusion Induction of labour for foetal growth restriction was not associated with an increased rate of caesarean section.
EVALuna2:212315

KI-gestützte Entscheidungsfindung in der Geburtshilfe – eine Machbarkeitsstudie über die medizinische Genauigkeit und Zuverlässigkeit von ChatGPT - Bader, Simon; Schneider, Michael; Psilopatis, Iason; Anetsberger, Daniel; Emons, Julius; Kehl, Sven (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
The aim of this study is to investigate the feasibility of artificial intelligence in the interpretation and application of medical guidelines to support clinical decision-making in obstetrics. ChatGPT was provided with guidelines on specific obstetric issues. Using several clinical scenarios as examples, the AI was then evaluated for its ability to make accurate diagnoses and appropriate clinical decisions. The results varied, with ChatGPT providing predominantly correct answers in some fictional scenarios but performing inadequately in others. Despite ChatGPT's ability to grasp complex medical information, the study revealed limitations in the precision and reliability of its interpretations and recommendations. These discrepancies highlight the need for careful review by healthcare professionals and underscore the importance of clear, unambiguous guideline recommendations. Furthermore, continuous technical development is required to harness artificial intelligence as a supportive tool in clinical practice. Overall, while the use of AI in medicine shows promise, its current suitability primarily lies in controlled scientific settings due to potential error susceptibility and interpretation weaknesses, aiming to safeguard the safety and accuracy of patient care.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Artificial intelligence; ChatGPT; labor induction; medical guidelines; obstetrics

Labour Induction with Misoprostol in German Obstetric Clinics: What Are the Facts on Such Use? - Kehl, Sven; Weiss, Christel; Rath, Werner; Schneider, Michael; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Stelzl, Patrick (Geburtshilfe und Frauenheilkunde, 2021)
Subject While the synthetic prostaglandin E1 analogue misoprostol is the most effect labour induction agent, its use is off-label for the most part. For this reason, and in view of its potential adverse effects and varying approaches to its administration, the drug has recently once again become a focus of critical attention. The objective of this survey was thus to establish a record of labour induction with misoprostol in German clinics and determine the impact of the negative reporting on everyday obstetric practice.
CRIS-Team WoS Importer:2021-09-03

Lack of evidence for effects of lockdowns on stillbirth rates during the SARS-CoV-2 pandemic in Bavaria: analysis of the Bavarian perinatal survey from 2010 to 2020 - Stumpfe, Florian; Schneider, Michael; Antoniadis, Sophia; Mayr, Andreas; Fleckenstein, Tobias; Staerk, Christian; Kehl, Sven; Hermanek, Peter; Boehm, Julian; Scharl, Anton; Beckmann, Matthias; Hein, Alexander (Archives of Gynecology and Obstetrics, 2022)
Background: Internationally, potential effects of national SARS-CoV-2-related lockdowns on stillbirth rates have been reported, but data for Germany, including risk factors for fetal pregnancy outcome, are lacking. The aim of this study is to compare the stillbirth rates during the two first lockdown periods in 2020 with previous years from 2010 to 2019 in a large Bavarian cohort. Methods: This study is a secondary analysis of the Bavarian perinatal data from 2010 to 2020, including 349,245 births. Univariate and multivariable regression analyses were performed to investigate the effect of two Bavarian lockdowns on the stillbirth rate in 2020 compared to the corresponding periods from 2010 to 2019. Results: During the first lockdown, the stillbirth rate was significantly higher compared to the reference period (4.04 vs. 3.03 stillbirths per 1000 births; P = 0.03). After adjustment for seasonal and long-term trends, this effect can no longer be observed (P = 0.2). During the second lockdown, the stillbirth rate did not differ in univariate (3.46 vs. 2.93 stillbirths per 1000 births; P = 0.22) as well as in multivariable analyses (P = 0.68), compared to the years 2010 to 2019. Conclusion: After adjustment for known long-term effects, in this study we did not find evidence that the two Bavarian lockdowns had an effect on the rate of stillbirths.
CRIS-Team Scopus Importer:2022-11-25
Keywords: COVID-19; Stillbirths; Stillborn

Low-dose Oral Misoprostol after Cervical Ripening with a Double-balloon Catheter: 25 μg or 50 μg? Niedrig dosiertes orales Misoprostol nach Zervixreifung mit dem Doppelballonkatheter: 25 μg oder 50 μg? - Kehl, Sven; Karademir, Zeynep Selen; Weiss, Christel; Titzmann, Adriana; Schneider, Michael; Beckmann, Matthias; Bader, Simon (Geburtshilfe und Frauenheilkunde, 2025)
Purpose Misoprostol is used in low doses for the induction of labor. It is still not clear, however, which of the approved doses (25 μg or 50 μg) is more beneficial. The aim of this study was to investigate whether oral misoprostol at a dose of 25 μg or at a dose of 50 μg should be preferred to induce labor after cervical ripening with a double-balloon catheter. Material and Methods This retrospective cohort study analyzed full-term pregnancies (≥ 37 + 0 GW) in which sequential induction of labor was carried out using a double-balloon catheter followed by oral administration of misoprostol. The patients were divided into two groups: Group 1 received 50 μg misoprostol every four hours and Group 2 received 25 μg misoprostol every two hours. The primary target parameter was the rate of caesarean sections. Secondary target parameters included the interval from induction to delivery, the rate of spontaneous births, vaginal operative deliveries, and neonatal outcomes. Results 967 patients were included in the study: 514 in Group 1 and 453 in Group 2. There was no significant difference in the rate of caesarean sections between the two groups (p = 0.688). However, significantly more women in Group 2 had unsuccessful induction of labor, defined as a vaginal birth after 72 hours (15.8% vs. 8.1%, p = 0.001). But fewer neonates from Group 2 required transfer to the neonatal department (10.6% vs. 18.5%, p < 0.001). Conclusion The study found no difference in the rate of caesarean sections for the different doses of misoprostol. However the rate of vaginal deliveries only occurring after 72 hours was higher in the group treated with 25 μg misoprostol, while more neonates required transfer to the neonatal department in the group receiving 50 μg misoprostol.
CRIS-Team Scopus Importer:2025-03-14
Keywords: caesarean section; double-balloon cervical ripening catheter; induction of labor; misoprostol; neonatal outcome

Maternal SARS-CoV-2 infection during pregnancy: possible impact on the infant - Morhart, Patrick; Mardin, Christian; Rauh, Manfred; Juengert, Joerg; Hammersen, Johanna; Kehl, Sven; Schuh, Wolfgang; Maier-Wohlfart, Sigrun; Hermes, Katharina; Neubert, Antje; Schneider, Michael; Hein, Alexander; et al. (European Journal of Pediatrics, 2021)
The risk and potential consequences of mother-to-child transmission of severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) during pregnancy are still a matter of debate. We studied the impact of SARS-CoV-2 infection on 56 complete households, including 27 newborns whose mothers were pregnant when exposed to the virus. Two PCR-confirmed perinatal SARS-CoV-2 transmissions with mild symptoms in affected neonates were recorded. In addition, we observed a severe eye malformation (unilateral microphthalmia, optic nerve hypoplasia, and congenital retinopathy) associated with maternal SARS-CoV-2 infection in weeks 5 and 6 of embryonic development. This embryopathy could not be explained by other infectious agents, genetic factors, drug use, or maternal disease during pregnancy. Eight other women with a history of SARS-CoV-2 infection prior to gestational week 12, however, delivered healthy infants. Conclusion: The repeated occurrence of mother-to-child transmission in our cohort with risks that remain incompletely understood, such as long-term effects and the possibility of an embryopathy, should sensitize researchers and stimulate further studies as well as support COVID-19 vaccination recommendations for pregnant women. Trial registration number: NCT04741412. Date of registration: November 18, 2020What is Known:•Materno-fetal transmission of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) during pregnancy has rarely been reported so far, but was demonstrated in isolated cases.What is New:•In a study of complete households with documented SARS-CoV-2 infection, including a cohort of pregnant women, we observed perinatal coronavirus transmission at a higher frequency than expected.•We also describe a newborn boy with an eye malformation reminiscent of rubella embryopathy but associated with early gestation SARS-CoV-2 infection of his mother.•A coronavirus-related embryopathy, reported here for the first time, is a finding that requires further investigation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Case report; Coronavirus; Embryopathy; Malformation; Materno-fetal transmission

Orofacial clefts alter early life oral microbiome maturation towards higher levels of potentially pathogenic species: A prospective observational study - Seidel, Corinna Lesley; Strobel, Karin; Weider, Matthias; Tschaftari, Marco; Unertl, Christoph; Willershausen, Ines; Weber, Manuel; Hörning, André; Morhart, Patrick; Schneider, Michael; Beckmann, Matthias; Bogdan, Christian; et al. (Journal of Oral Microbiology, 2023)
Orofacial clefts (OFC) present different phenotypes with a postnatal challenge for oral microbiota development. In order to investigate the impact of OFC on oral microbiota, smear samples from 15 neonates with OFC and 17 neonates without OFC were collected from two oral niches (tongue, cheek) at two time points, i.e. after birth (T0: Ø3d OFC group; Ø2d control group) and 4–5 weeks later (T1: Ø32d OFC group; Ø31d control group). Subsequently, the samples were analyzed using next-generation sequencing. We detected a significant increase of alpha diversity and anaerobic and Gram-negative species from T0 to T1 in both groups. Further, we found that at T1 OFC neonates presented a significantly lower alpha diversity (lowest values for high cleft severity) and significantly higher levels of Enterobacteriaceae (Citrobacter, Enterobacter, Escherichia-Shigella, Klebsiella), Enterococcus, Bifidobacterium, Corynebacterium, Lactocaseibacillus, Staphylococcus, Acinetobacter and Lawsonella compared to controls. Notably, neonates with unilateral and bilateral cleft lip and palate (UCLP/BCLP) presented similarities in beta diversity and a mixture with skin microbiota. However, significant differences were seen in neonates with cleft palate only compared to UCLP/BCLP with higher levels of anaerobic species. Our findings revealed an influence of OFC as well as cleft phenotype and severity on postnatal oral microbiota maturation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: early life dysbiosis; microbiome maturation; neonates; oral microbiome; Orofacial clefts

Orofacial clefts lead to increased pro-inflammatory cytokine levels on neonatal oral mucosa - Seidel, Corinna Lesley; Percivalle, Elena; Tschaftari, Marco; Weider, Matthias; Strobel, Karin; Willershausen, Ines; Unertl, Christoph; Schmetzer, Helga M.; Weber, Manuel; Schneider, Michael; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Immunology, 2022)
Orofacial clefts (OFC) are frequent congenital malformations characterized by insufficient separation of oral and nasal cavities and require presurgical infant orthopedics and surgical interventions within the first year of life. Wound healing disorders and higher prevalence of gingivitis and plaque levels are well-known challenges in treatment of children with OFC. However, oral inflammatory mediators were not investigated after birth using non-invasive sampling methods so far. In order to investigate the impact of OFC on oral cytokine levels, we collected tongue smear samples from 15 neonates with OFC and 17 control neonates at two time points (T), T0 at first consultation after birth, and T1, 4 to 5 weeks later. The samples were analyzed using multiplex immunoassay. Overall, we found significantly increased cytokine levels (TNF, IL-1β/-2/-6/-8/-10) in tongue smear samples from neonates with OFC compared to controls, especially at T0. The increase was even more pronounced in neonates with a higher cleft severity. Further, we detected a significant positive correlation between cleft severity score and distinct pro-inflammatory mediators (GM-CSF, IL-1β, IL-6, IL-8) at T0. Further, we found that breast-milk (bottle) feeding was associated with lower levels of pro-inflammatory cytokines (IL-6/-8) in neonates with OFC compared to formula-fed neonates. Our study demonstrated that neonates with OFC, especially with high cleft severity, are characterized by markedly increased inflammatory mediators in tongue smear samples within the first weeks of life potentially presenting a risk for oral inflammatory diseases. Therefore, an inflammatory monitoring of neonates with (severe) OFC and the encouragement of mother to breast-milk (bottle) feed might be advisable after birth and/or prior to cleft surgery.
CRIS-Team Scopus Importer:2022-12-16
Keywords: cleft lip and palate; cytokines; mucosal homeostasis; mucosal immunity; neonates; oral; oral inflammation; orofacial clefts

Outcome of pregnancies with recent primary cytomegalovirus infection in first trimester treated with hyperimmunoglobulin: observational study - Kagan, K. O.; Enders, M.; Hoopmann, M.; Geipel, A.; Simonini, C.; Berg, C.; Gottschalk, I.; Faschingbauer, Florian; Schneider, Michael; Ganzenmueller, T.; Hamprecht, K. (Ultrasound in Obstetrics & Gynecology, 2021)
Objective: To examine the efficacy of hyperimmunoglobulin (HIG) treatment in women with a recent primary cytomegalovirus (CMV) infection up to 14 weeks' gestation. Methods: This is an ongoing observational study conducted at the prenatal medicine departments of the University Hospitals of Tübingen, Bonn, Cologne and Erlangen, Germany, as well as at the Laboratory Prof. Gisela Enders and Colleagues in Stuttgart, Germany and the Institute for Medical Virology at the University of Tübingen, Tübingen, Germany. Enrolment criteria were the presence of confirmed recent primary CMV infection in the first trimester and a gestational age at first HIG administration of ≤ 14 weeks. The following inclusion criteria indicated a recent primary infection: low anti-immunoglobulin (Ig)-G levels, low anti-CMV-IgG avidity in the presence of a positive CMV-IgM test and no positive reactivity or just seroconversion anti-gB2-IgG-reactivity. HIG administration was started as soon as possible within a few days after the first visit. HIG was administered intravenously at a dose of 200 IU/kg maternal body weight and repeated every 2 weeks until about 18 weeks' gestation. The primary outcome was maternal–fetal transmission at the time of amniocentesis. Multivariate logistic regression analysis was used to determine significant covariates that could predict maternal–fetal transmission. Results: We included 149 pregnancies (153 fetuses) that completed the treatment. Median maternal age and weight were 32.0 years and 65.0 kg, respectively. Median gestational age at the time of first referral to one of the four centers was 9.4 weeks. Median anti-CMV-IgG level, anti-CMV-IgM index and CMV-IgG avidity were 5.7 U/mL, 2.5 and 22.3%, respectively. HIG treatment was started at a median gestational age of 10.6 weeks and ended at a median of 17.9 weeks. Within this time frame, HIG was administered on average four times in each patient. Amniocentesis was carried out at a median gestational age of 20.4 weeks. In 143 (93.5%) of the 153 cases, the fetus was not infected. Maternal–fetal transmission occurred in 10 cases (6.5% (95% CI, 3.2–11.7%)). On uni- and multivariate logistic regression analysis, the level of anti-IgM index was the only factor associated significantly with maternal–fetal transmission at amniocentesis. However, only four (40.0%) of the 10 cases with maternal–fetal transmission had an anti-IgM index above 11.4, which corresponds to the 95th centile of pregnancies without transmission. Conclusions: HIG is a treatment option to prevent maternal–fetal transmission in pregnancy with a primary CMV infection. However, HIG treatment seems to be beneficial primarily in women with a recent primary infection in the first trimester or during the periconceptional period, and when it is administered at a biweekly dose of 200 IU/kg. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.
CRIS-Team Scopus Importer:2021-03-26
Keywords: cytomegalovirus; hyperimmunoglobulin; outcome; pregnancy

Perinatal Outcome in Pregnant Women With Isolated Oligohydramnios Diagnosed With the Single Deepest Pocket Method - Dammer, Ulf; Pretscher, Jutta; Weiss, Christel; Schneider, Michael; Faschingbauer, Florian; Beckmann, Matthias; Kehl, Sven (In Vivo, 2024)
AIM: The aim of this study was to investigate perinatal outcome in singleton pregnancies at term with isolated oligohydramnios, diagnosed by using the single deepest pocket method. PATIENTS AND METHODS: In this historic cohort study, the perinatal outcomes of 196 women with isolated oligohydramnios at term, diagnosed by using the single deepest pocket method, were compared to 8,676 women with normal amniotic fluid volume. The primary outcome measure was the Cesarean section rate. Further outcome parameters included the rate of induction of labor, abnormal cardiotocography, umbilical cord pH and base excess, Apgar, meconium-stained liquor and admission to neonatal intensive care unit. RESULTS: In the group with isolated oligohydramnios, there were significantly more Cesarean sections (p=0.0081) and more abnormal cardiotocographies (p=0.0005). Univariate and multivariate analyses showed that this difference was seen particularly in nulliparous women (p=0.0025 for Cesarean section and 0.0368 for abnormal cardiotocography). Peripartal and perinatal outcome parameters were not different between the two groups. CONCLUSION: In women with isolated oligohydramnios at term, there is no impact on fetal outcome. The influence of isolated oligohydramnios on the rate of cesarean section and abnormal cardiotocography is considered to be less than that of parity.
CRIS-Team Scopus Importer:2024-03-15
Keywords: abnormal cardiotocography; amniotic fluid; Cesarean section; Oligohydramnios; perinatal outcome; SDP; single deepest pocket

Predicting attention deficit hyperactivity disorder using pregnancy and birth characteristics - Schwenke, Eva; Fasching, Peter; Faschingbauer, Florian; Pretscher, Jutta; Kehl, Sven; Peretz, Roberta; Keller, Andrea; Häberle, Lothar; Eichler, Anna; Irlbauer-Müller, Viktoria; Dammer, Ulf; Beckmann, Matthias; et al. (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: The aim of this study was to evaluate maternal, prenatal, perinatal, and postpartum parameters as risk factors for the later development of an attention deficit hyperactivity disorder (ADHD) in the child. METHODS: Women who had given birth at Erlangen University Hospital between 1996 and 1999 were sent a questionnaire in 2009. The results of the questionnaire were correlated with the prospectively collected data for the births in 1996-1999. RESULTS: A total of 573 mother and child pairs were analyzed. Forty-four of the mothers reported that their child had ADHD (7.7%). No significant associations were found for the following parameters: mother's age; mother's educational level; number of the pregnancy; maternal weight before and at the end of pregnancy; mother's height; alcohol consumption during pregnancy; mode of delivery; gestational week; birthweight; umbilical artery blood values; Apgar score at 5 and 10 min; or breastfeeding. The parameters of smoking in pregnancy and an Apgar score lower than 7 after 1 min were significantly associated with a risk for later development of ADHD. CONCLUSIONS: This analysis of maternal, prenatal, perinatal, and postnatal parameters found that smoking in pregnancy and a low Apgar score 1 min after birth are associated with a significantly greater risk for the development of ADHD. Beyond the question of the causal mechanism involved, this is a relevant finding, since smoking during pregnancy is a preventable risk factor.
EVALuna2:36367

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting. Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan-Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator. Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10-0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%. Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patients' labour.
CRIS-Team Scopus Importer:2022-02-25
Keywords: COVID-19; infection; pregnancy; prevalence; SARS-CoV-2

RANKL and OPG and their influence on breast volume changes during pregnancy in healthy women - Wunderle, Marius; Rübner, Matthias; Häberle, Lothar; Schwenke, Eva; Hack, Carolin; Bayer, Christian M.; Koch, Martin; Schwitulla, Judith; Schulz-Wendtland, Rüdiger; Kozieradzki, Ivona; Lux, Michael P.; Beckmann, Matthias; et al. (Scientific Reports, 2020)
Breast cancer risk is reduced by number of pregnancies and breastfeeding duration, however studies of breast changes during or after pregnancy are rare. Breast volume changes - although not linked to breast cancer risk - might be an interesting phenotype in this context for correlative studies, as changes of breast volume vary between pregnant women. Serum receptor activator of nuclear factor kappa B ligand (RANKL) and its antagonist osteoprotegerin (OPG) were measured prospectively before gestational week 12, and three-dimensional breast volume assessments were performed. A linear regression model including breast volume at the start of pregnancy, RANKL, OPG, and other factors was used to predict breast volume at term. The mean breast volume was 413 mL at gestational week 12, increasing by a mean of 99 mL up to gestational week 40. In addition to body mass index and breast volume at the beginning of pregnancy, RANKL and OPG appeared to influence breast volume with a mean increase by 32 mL (P = 0.04) and a mean reduction by 27 mL (P = 0.04), respectively. Linking the RANKL/RANK/OPG pathway with breast volume changes supports further studies aiming at analysing breast changes during pregnancy with regard to breast cancer risk.
CRIS-Team Scopus Importer:2020-03-31

Recommendations of the AGG (Working Group for Obstetrics, Department of Maternal Diseases) on How to Treat Thyroid Function Disorders in Pregnancy. - Hamza, Amr; Schlembach, Dietmar; Schild, Ralf Lothar; Groten, Tanja; Wölfle, Joachim; Battefeld, Wilgard; Kehl, Sven; Schneider, Michael (Geburtshilfe und Frauenheilkunde, 2023)
Objective These recommendations from the AGG (Committee for Obstetrics, Department of Maternal Diseases) on how to treat thyroid function disorder during pregnancy aim to improve the diagnosis and management of thyroid anomalies during pregnancy. Methods Based on the current literature, the task force members have developed the following recommendations and statements. These recommendations were adopted after a consensus by the members of the working group. Recommendations The following manuscript gives an insight into physiological and pathophysiological thyroid changes during pregnancy, recommendations for clinical and subclinical hypo- and hyperthyroidism, as well as fetal and neonatal diagnostic and management strategies.
EVALuna2:548561

Risk of postmenopausal hormone therapy and patient history factors for the survival rate in women with endometrial carcinoma - Hein, Alexander; Schneider, Michael; Renner, Stefan; Fasching, Peter; Fießler, Cornelia; Titz, Susanna; Hartmann, Arndt; Beckmann, Matthias; Thiel, Falk C. (Archives of Gynecology and Obstetrics, 2019)
Purpose: Postmenopausal hormone therapy (HT) is known to affect the development of hormone-dependent endometrial carcinoma (type I EC). Several studies on breast and ovarian carcinoma have shown that HT influences the molecular profile and prognostic behavior of these tumors. This study aimed to investigate the influence of prior HT and other risk factors on the prognosis in a cohort of patients with invasive endometrial carcinoma (EC). Methods: Among 525 patients diagnosed with EC between 1987 and 2010, 426 postmenopausal patients were identified. Information regarding HT was available in 287 of these patients, 78 of whom had a history of HT and 209 of whom did not. Both overall survival (OS) and progression-free survival (PFS) were analyzed. In addition to OS and PFS, risk factors such as age at diagnosis, postmenopausal HT, body mass index (BMI), diabetes mellitus, tumor stage, EC type (I or II), and recurrences were analyzed. Results: Relative to HT alone, women with EC and a history of HT had a longer survival than those with no HT. However, the Cox proportional hazards model showed that it was not HT itself, but rather other characteristics in the HT group that were causally associated with longer survival. Conclusions: Age (the older, the worse) and tumor stage (the higher, the worse) were significant influences on overall survival. Patients with HT also had lower BMIs, less diabetes, more type I EC, and fewer recurrences in comparison with the non-HT group. With regard to the PFS, it made no difference whether the patient was receiving HT.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Endometrial carcinoma; Estrogen; Hormone replacement therapy; Hormone therapy; Overall survival; Progesterone; Prognosis; Risk factors

SARS-CoV-2 Infection in Pregnancy - a Review of the Current Literature and Possible Impact on Maternal and Neonatal Outcome - Stumpfe, Florian; Titzmann, Adriana; Schneider, Michael; Stelzl, Patrick; Kehl, Sven; Fasching, Peter; Beckmann, Matthias; Enßer, Armin (Geburtshilfe und Frauenheilkunde, 2020)
In December 2019, cases of pneumonia of unknown cause first started to appear in Wuhan in China; subsequently, a new coronavirus was soon identified as the cause of the illness, now known as Coronavirus Disease 2019 (COVID-19). Since then, infections have been confirmed worldwide in numerous countries, with the number of cases steadily rising. The aim of the present review is to provide an overview of the new severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2) and, in particular, to deduce from it potential risks and complications for pregnant patients. For this purpose, the available literature on cases of infection in pregnancy during the SARS epidemic of 2002/2003, the MERS (Middle East respiratory syndrome) epidemic ongoing since 2012, as well as recent publications on cases infected with SARS-CoV-2 in pregnancy are reviewed and reported. Based on the literature available at the moment, it can be assumed that the clinical course of COVID-19 disease may be complicated by pregnancy which could be associated with a higher mortality rate. It may also be assumed at the moment that transmission from mother to child in utero is unlikely. Breastfeeding is possible once infection has been excluded or the disease declared cured.
CRIS-Team Scopus Importer:2020-05-19
Keywords: 2019-nCoV; coronavirus; COVID-19; pregnancy; SARS-CoV-2

Schilddrüsenfunktionsstörungen in der Schwangerschaft - Hamza, Amr; Schlembach, Dietmar; Schild, Ralf Lothar; Groten, Tanja; Wölfle, Joachim; Battefeld, Wilgard; Kehl, Sven; Schneider, Michael (gynäkologische praxis, 2024)
With the onset of pregnancy, TSH values fall then rise with ongoing gestation. A TSH screening should be performed in the first trimester under certain indications. Furthermore, the TPO-Ab status should be determined when the TSH levels exceeds 2.5 mU/l as it might lower threshold of a levothyroxine (LT4) substitution. Subclinical hypothyroidism is associated with an increased risk of miscarriage, preterm birth but not an increased risk of preeclampsia, fetal growth restriction or adverse neonatal neurocognitive outcomes and may not require a supplementation especially with negative TPO-Ab. However, the overt hypothyroidism requires LT4 administration. A manifest hyperthyroidism necessitates treatment adjustments before and with the onset pregnancy. Propylthiouracil is recommended in the first trimester and replaced by with thiamazole in the second trimester. A thorough birth plan with neonatological management should be planned. In cases of a fetal hyperthyroidism, a vertical treatment should be introduced in perinatal centres with a specialized experience. Regarding birth management, a detailed intra- and postnatal management plan, including a specialized paediatric care, is necessary. Fetal hyperthyroidism should be ruled out prenatally upon taking thyrostatic agents during the first trimester. Intrauterine therapies for fetal hyper- and hypothyroidism should only be carried out after careful consideration in centres with a therapeutic expertise. In complex cases, the birth should occur in a prenatal centre with paediatric personal that have the necessary expertise.
CRIS-Team Scopus Importer:2024-08-23
Keywords: hyperthyroidism; hypothyroidism; thyroid disease; TSH

The FANCM:p.Arg658* truncating variant is associated with risk of triple-negative breast cancer - Figlioli, Gisella; Bogliolo, Massimo; Catucci, Irene; Caleca, Laura; Lasheras, Sandra Viz; Pujol, Roser; Kiiski, Johanna I.; Muranen, Taru A.; Barnes, Daniel R.; Dennis, Joe; Michailidou, Kyriaki; Bolla, Manjeet K.; et al. (npj Breast Cancer, 2019)
Breast cancer is a common disease partially caused by genetic risk factors. Germline pathogenic variants in DNA repair genes BRCA1, BRCA2, PALB2, ATM, and CHEK2 are associated with breast cancer risk. FANCM, which encodes for a DNA translocase, has been proposed as a breast cancer predisposition gene, with greater effects for the ER-negative and triple-negative breast cancer (TNBC) subtypes. We tested the three recurrent protein-truncating variants FANCM:p.Arg658*, p.Gln1701*, and p.Arg1931* for association with breast cancer risk in 67,112 cases, 53,766 controls, and 26,662 carriers of pathogenic variants of BRCA1 or BRCA2. These three variants were also studied functionally by measuring survival and chromosome fragility in FANCM−/− patient-derived immortalized fibroblasts treated with diepoxybutane or olaparib. We observed that FANCM:p.Arg658* was associated with increased risk of ER-negative disease and TNBC (OR = 2.44, P = 0.034 and OR = 3.79; P = 0.009, respectively). In a country-restricted analysis, we confirmed the associations detected for FANCM:p.Arg658* and found that also FANCM:p.Arg1931* was associated with ER-negative breast cancer risk (OR = 1.96; P = 0.006). The functional results indicated that all three variants were deleterious affecting cell survival and chromosome stability with FANCM:p.Arg658* causing more severe phenotypes. In conclusion, we confirmed that the two rare FANCM deleterious variants p.Arg658* and p.Arg1931* are risk factors for ER-negative and TNBC subtypes. Overall our data suggest that the effect of truncating variants on breast cancer risk may depend on their position in the gene. Cell sensitivity to olaparib exposure, identifies a possible therapeutic option to treat FANCM-associated tumors.
CRIS-Team Scopus Importer:2019-11-12

The role of artificial intelligence in gynecologic and obstetric emergencies - Psilopatis, Iason; Heindl, Felix; Cupisti, Susanne; Fischer, Ulrike; Kohlmann, Valentina; Schneider, Michael; Bader, Simon; Krückel, Annika; Emons, Julius (European Journal of Obstetrics Gynecology and Reproductive Biology, 2025)
Objective: To investigate the potential of artificial intelligence (AI) in emergency medicine, focusing on its utility in triaging and managing acute gynecologic and obstetric emergencies. Methods and Materials: This feasibility study assessed Chat-GPT's performance in triaging and recommending management interventions for gynecologic and obstetric emergencies, using ten fictive cases. Five common conditions were modeled for each specialty. Chat-GPT was tasked with proposing triage classifications and providing immediate management recommendations. Human experts independently reviewed each case, classified triage categories, and proposed management. Following this, experts evaluated Chat-GPT's recommendations, rating the AI's responses on accuracy and clinical applicability. Results: Chat-GPT's recommendations demonstrated high concordance with human evaluators. Chat-GPT's triage classifications matched those of human experts in most cases, though minor discrepancies in urgency ratings were observed. The AÍs suggestions were mostly rated as “very good” to “excellent.” While Chat-GPT consistently delivered appropriate responses, some human evaluators noted slight differences in perceived urgency. Conclusions: This study highlights Chat-GPT's potential as a clinical support tool in emergency medicine. Chat-GPT provided structured, evidence-based recommendations comparable to those of experienced clinicians, especially for high-stakes gynecologic and obstetric emergencies. Although encouraging, these results highlight the value of utilizing AI in addition to human knowledge, as variations in urgency ratings and management nuances highlight the necessity of human supervision in crucial decision-making.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Artificial intelligence; Clinical practice; Emergency; Gynecologic; Obstetric

Toxoplasma gondii Infection in Pregnancy - Recommendations of the Working Group on Obstetrics and Prenatal Medicine (AGG - Section on Maternal Disorders) - Schneider, Michael; Faschingbauer, Florian; Kagan, Karl Oliver; Groβ, Uwe; Enders, Martin; Kehl, Sven (Geburtshilfe und Frauenheilkunde, 2023)
Aim The AGG (Working Group for Obstetrics and Prenatal Diagnostics, Section Maternal Diseases) has issued these recommendations to improve the detection and management of Toxoplasma gondii infection in pregnancy. Methods Members of the Task Force developed the recommendations and statements presented here using recently published literature. The recommendations were adopted after a consensus process by members of the working group. Recommendations This article focuses on the epidemiology and pathophysiology of Toxoplasma gondii infection in pregnancy and includes recommendations for maternal and fetal diagnosis, transmission prophylaxis, therapy, prevention, screening, and peripartum management.
CRIS-Team Scopus Importer:2023-10-20
Keywords: congenital toxoplasmosis; pregnancy; therapy; Toxoplasma gondii; transmission

Trial of labor after caesarean section in low risk pregnancies: is it risky? - Kehl, Sven; Düster, Hanna; Weiss, Christel; Bader, Simon; Schneider, Michael; Beckmann, Matthias; Dammer, Ulf; Pretscher, Jutta (Archives of Gynecology and Obstetrics, 2024)
Purpose: To evaluate the influence of a previous caesarean section on adverse composite maternal and perinatal outcome in women who attempted a trial of labor. Methods: This historical cohort study analyzed maternal and perinatal outcome in women with otherwise low risk pregnancies at term who underwent a trial of labor after a caesarean section (TOLAC). The primary outcome measure was the adverse composite outcome. Secondary outcome measures were amongst others the caesarean section rate and the mode of vaginal delivery. Results: The adverse composite outcome was more frequently in the previous caesarean section group compared to women with no previous caesarean Sect. (22.3% vs. 15.6%, p < 0.0001). The percentage of caesarean Sect. (15.4% vs. 8.2%, p < 0,0001), uterine rupture (1.0% vs. 0.02%, p < 0.0001), placental abruption (1.1% vs. 0.3%, p = 0.0014), vaginal operative delivery (16.0% vs. 8.6%, p < 0.0001), pH < 7.10 (3.7% vs. 2.5%, p = 0.0151), base excess < -12 (3.2% vs. 2.2%, p = 0.0297), abnormal cardiotocography (22.5% vs. 13.9%, p < 0,0001) and fetal blood analysis (6.2% vs. 2.6%, p < 0.0001) was significantly higher in women with a previous caesarean section. Taking the parity into account, these differences could only been seen in women without a previous vaginal delivery. In parous women with a previous vaginal delivery and a caesarean section in history, the adverse composite did not differ between the groups. Only the rate of pH < 7.1 was higher in women after a caesarean Sect. (4.5% vs. 1.8%, p = 0.0436). Conclusion: Trial of labor after caesarean in otherwise low risk pregnancies is associated with a higher rate of complications especially if there is no history of vaginal delivery.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Caesarean section rate; Composite adverse outcome; Prior caesarean section; TOLAC; Uterine rupture; VBAC

Two truncating variants in FANCC and breast cancer risk - Dork, Thilo; Peterlongo, Paolo; Mannermaa, Arto; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Ahearn, Thomas; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Aronson, Kristan J.; Augustinsson, Annelie; et al. (Scientific Reports, 2019)
Fanconi anemia (FA) is a genetically heterogeneous disorder with 22 disease-causing genes reported to date. In some FA genes, monoallelic mutations have been found to be associated with breast cancer risk, while the risk associations of others remain unknown. The gene for FA type C, FANCC, has been proposed as a breast cancer susceptibility gene based on epidemiological and sequencing studies. We used the Oncoarray project to genotype two truncating FANCC variants (p.R185X and p.R548X) in 64,760 breast cancer cases and 49,793 controls of European descent. FANCC mutations were observed in 25 cases (14 with p.R185X, 11 with p.R548X) and 26 controls (18 with p.R185X, 8 with p.R548X). There was no evidence of an association with the risk of breast cancer, neither overall (odds ratio 0.77, 95%CI 0.44–1.33, p = 0.4) nor by histology, hormone receptor status, age or family history. We conclude that the breast cancer risk association of these two FANCC variants, if any, is much smaller than for BRCA1, BRCA2 or PALB2 mutations. If this applies to all truncating variants in FANCC it would suggest there are differences between FA genes in their roles on breast cancer risk and demonstrates the merit of large consortia for clarifying risk associations of rare variants.
CRIS-Team Scopus Importer:2019-09-17